The Effectiveness of Community Circle Strategy on Students English Speaking Skill of The Tenth Grade at MA Al Balagh Bulutigo - Khofifah; Moh. Arifin; M. Labib Al Halim (FKIP, Universitas Billfath Lamongan, 2024)
This research was supposed to evaluate the effectiveness of the Community Circle Strategy in enhancing students' English-speaking skills at MA Al Balagh. This research consists of 8 stages, including observation, pre-test examination at the second meeting, implementation of strategies, and post-test examination at the final meeting. The study was conducted on 24 students of class X at MA Al Balagh. The method employed was quantitative with a pre-experimental approach. Data from pre-tests and post-tests were examined for normality using the Kolmogorov-Smirnov test, indicating that the data were normally distributed. Further analysis utilized the T-test to determine significance (Sig.). The results of the T-test indicated that the significance value (p = 0.000) < ? (0.05), suggesting insufficient evidence to reject the null hypothesis (H0), thus accepting the alternative hypothesis (Ha). This indicated a significant improvement in students' vocabulary mastery following the treatment. These findings affirm that employing the Community Circle Strategy was effective in enhancing students' speaking skills.